Impact of inclusive leadership on adaptive performance: The role of innovative work behaviour - Mohammad Saleh Enaizan Bataineh; Siti-Rohaida Mohamed Zainal; Rajendran Muthuveloo; Raheel Yasin; Joather Al Wali; Mohamed Ibrahim Mugableh (International Journal of Business Science & Applied Management (IJBSAM), 2022)
As an organizational behaviour, job performance can be described from two perspectives, namely organizational citizenship behaviour and task performance. To enhance the concept of job performance, especially in servicing jobs (e.g., nursing), recent literature has considered the construct of adaptive performance. Thus, the major purpose of this research is to analyze the nexus between inclusive leadership (IL) and adaptive performance (AP) among private hospital nurses in Jordan using innovative work behaviour (IWB) as a mediating variable. Our study uses questionnaires to collect data from 169 nurses who work in different private hospitals in Jordan. The nature of the study is quantitative and cross-sectional, with individuals as the unit of analysis. The survey questionnaires, which consist of measures of IL, AP, and IWB, were distributed to the full-time nurses in the hospitals. The empirical outcomes show that IL has a direct and significant predictive effect on AP, and an indirect predictive effect through innovative work behaviour. This study discusses the practical and theoretical implications of the empirical results. The outcomes of this study could help practitioners and policy makers to create effective IL and IWB that can enhance employees' adaptability towards their organization with a view to boosting their AP.
Keywords: 650; inclusive leadership (IL); innovative work behaviour (IWB); adaptive performance (AP)